2009
DOI: 10.1007/s00041-009-9072-2
|View full text |Cite
|
Sign up to set email alerts
|

Simple Proofs of Nowhere-Differentiability for Weierstrass’s Function and Cases of Slow Growth

Abstract: ABSTRACT. Using a few basics from integration theory, a short proof of nowhere-differentiability of Weierstrass functions is given. Restated in terms of the Fourier transformation, the method consists in principle of a second microlocalisation, which is used to derive two general results on existence of nowhere differentiable functions. Examples are given in which the frequencies are of polynomial growth and of almost quadratic growth as a borderline case.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Multiple proofs of the Weierstrass function's non-differentiability at all points have been published; several of these use Fourier Series, which goes beyond the space constraints of this paper (and the time constraints of its author). For a complete proof of Theorem 2, reference [6,7].…”
Section: Proof Of Uniform Continuity and Nowhere Differentiabilitymentioning
confidence: 99%
“…Multiple proofs of the Weierstrass function's non-differentiability at all points have been published; several of these use Fourier Series, which goes beyond the space constraints of this paper (and the time constraints of its author). For a complete proof of Theorem 2, reference [6,7].…”
Section: Proof Of Uniform Continuity and Nowhere Differentiabilitymentioning
confidence: 99%
“…Many authors found the fractional derivative of the continuous but nowhere differentiable function that is Weierstrass Function [10][11][12][13][14][15][16][17] using different type definitions of fractional derivatives. Here Jumarie type fractional order derivative of ( ) W x α α is of order α…”
Section: The Jumarie Fractional Derivative Of Fractional Weierstrass mentioning
confidence: 99%
“…On the other hand fractional calculus is another developing mathematical tool to study the continuous but non-differentiable functions (signals) where the conventional calculus fails [4][5][6][7][8][9][10][11]. Many authors are trying to relate between the fractional derivative and fractional dimension [1,[12][13][14][15]. The functions which are continuous but non-differentiable in integer order calculus can be characterized in terms of fractional calculus and especially through Holder exponent [10,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we study the uniform Hölder continuity of R α,β with β ≥ α − 1 in order to complete and generalize a result of Johnsen [19] in 2010 which claims that, if β > α−1, then R α,β is uniformly Hölder continuous with an exponent superior or equal to (α − 1)/β. To achieve this, we use some techniques different from the ones of Johnsen.…”
Section: Introductionmentioning
confidence: 99%